CYTOTOXIC AND CLASTOGENIC EVALUATION ON HUMAN LYMPHOCYTES OF A 5α, 8α-EPIDIOXYSTEROL - PAREJA, Andrés; PAREJA, Andrés; MARQUEZ F., María E.; MARQUEZ F., María E.; MARTÍNEZ M., Alejandro; MARTÍNEZ M., Alejandro (Vitae, 2009)
5α, 8α-epidioxysterol is obtained by photochemical oxidation of 7-dehydrocholesterol. This compound is analyzed using chromatographic and spectral techniques. This analysis identifies the compound as: 5α, 8α-epidioxy-cholesta-6-en-3β-ol. Cytotoxic and clastogenic effects of 5α, 8α-epidioxysterol by comet and exclusion assays with the tripan blue dye are evaluated. Three concentrations are used to determinate its effect on human lymphocytes from peripheral blood. No concentration shows clastogenic effect but the higher concentration exhibited cytotoxic effect. These results are interesting for this compound but it is necessary to do other in vitro and in vivo assays to evaluate the behavior on other cellular systems with the goal to determinate its bioactive potential.